Consumer emotions, perceived image and behavioral intentions toward Portuguese gastronomy - Moura, Ana de Oliveira Pais Costa (2015)
The main aim of the present dissertation was to study the general image of Portuguese traditional food, focusing on attribute perceptions, emotional responses and behavioral intentions of both Portuguese and Foreigners. Overall, we expected that Portuguese perceptions, emotions and behavioral intentions regarding traditional Portuguese food would differ from foreigners. Participants (N= 100 college students; 66 females, 44 males; 47 Portuguese and 53 foreigners; age between 18-65 years; M = 26.8 years), were asked to evaluate their emotional responses, attributes and behavioral intentions regarding 28 food images (14 traditional-Portuguese; 14 non-traditional), while skin conductance responses were being registered. Body dissatisfaction and food neophobia were also evaluated for control purposes. We found that although foreigners are familiar to Portuguese traditional food and consider it stimulating and tasty, they perceive it as unhealthy, difficult to prepare and to find. These results could be useful for the Portuguese gastronomy sectors to improve their image and focus on their target audience.